The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s10396-015-0670-0
|View full text |Cite
|
Sign up to set email alerts
|

Transverse ultrasound assessment of the flexor pollicis longus tendon movement on the distal radius during wrist and finger motion in distal radius fracture with volar plating

Abstract: This study showed that the wrist dorsal flexion position with finger flexion could be the appropriate position to examine FPL tendon irritation after plating. Moreover, it would be effective for preventing FPL rupture to cover the FPL transverse gliding area approximately 10 mm radial to the vertex of the palmar bony prominence of the distal radius with the pronator quadratus and the intermediate fibrous zone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…However, the ulnoradial FPL position can change up to 3 mm, depending on the wrist and finger position showing a maximal ulnodorsal shift from a radiovolar position in wrist extension with finger flexion. 13,14 Additionally, the plate notch seemed to limit the ulnar shift if the FPL tendon showed a tendon-plate contact. 14 In summary, the wrist position might change the amount of partial tendon-plate overlap.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the ulnoradial FPL position can change up to 3 mm, depending on the wrist and finger position showing a maximal ulnodorsal shift from a radiovolar position in wrist extension with finger flexion. 13,14 Additionally, the plate notch seemed to limit the ulnar shift if the FPL tendon showed a tendon-plate contact. 14 In summary, the wrist position might change the amount of partial tendon-plate overlap.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the FPL tendon course could just be estimated. Anatomical variations, wrist and finger positions 13,14,17 as well as X-ray rotation can also alter results and contribute to cases with a partial position of the tendon within the described corridor. Surgical fracture reduction and fixation might also change the position of the FPL tendon, potentially leading to a more ulnar position postoperatively than in healthy wrists.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, because of the plate thickness, anything that would move the tendons away from the plate is supposed to prevent tendon injuries. Nanno et al observed that the transverse gliding area of the FPL at the volar distal radius rim could be covered by the PQ suture to protect the FPL from attrition on the plate. Then, suturing the PQ may act as a protective sleeve to protect the flexor tendons on the distal part of the plate, even if the suture is partial or loose .…”
Section: Discussionmentioning
confidence: 99%
“…Most flexor tendon ruptures are caused by friction between the prominent volar distal edge of the plate and the flexor tendon. Recently, ultrasonography has become a useful method for early detection of FPL tendon attrition and prevention of FPL tendon rupture following volar locking plate fixation of distal radius fractures [8][9][10][11][12]. However, rarely, the volar locking plate itself entraps the FPL tendon entirely and causes its rupture, which has never been previously evaluated with ultrasonography.…”
Section: Introductionmentioning
confidence: 99%